Answer:
c
Step-by-step explanation:
For this question you can say d = 15 feet so we need the t then you can say :
15 = l 130 - 25t l ⇒ because of the absolute value you should say :
1) 130 - 25t = 15 ⇒ -25t = 15 - 130 ⇒ - 25t = -115 ⇒ t = 115/25 = 4.6 sec
2) 130 - 25t = - 15 ⇒ -25t = -15 - 130 ⇒ -25t = - 145 ⇒ t = 145/25 = 5.8 sec
so the answer is c :))
i hope this is helpful
Well, let's first solve each equation:
1.) -4x + 6 - 3x = 12 - 2x - 3x
To start, combine each like-term on each side of the equal sign (The numbers with variables in-common // the numbers alike on the same side of the equal sign):
-7x + 6 = 12 - 5x
Now, we get the two terms with variables attached to them, on the same side, so, we do the opposite of subtraction, which is, addition:
-7x + 6 = 12 - 5x
+5x +5x
_____________
-2x + 6 = 12
Next, you do the opposite of addition, which is, subtraction, and, subtract 6 from both sides:
-2x + 6 = 12
-6 -6
____________
-2x = 6
Finally, divide by -2 on each side, to find out what the value of 'x' is:
-2x = 6
÷-2 ÷-2
________
x = -3
So, the answer is not 'A.'
_________________________________________
Now, we test out the rest of the equations, the exact same way:
2.) 4x + 6 + 3x = 12 + 2x + 3x
Combine your like-terms, on each side of the equal sign:
7x + 6 = 12 + 5x
Now, get both terms, with the variable, 'x,' to the same side, and, to do that, do the opposite of addition, which is, subtraction:
7x + 6 = 12 + 5x
-5x -5x
______________
2x + 6 = 12
Next, subtract 6 from both sides:
2x + 6 = 12
-6 -6
__________
2x = 6
Finally, divide by 2, on both sides:
2x = 6
÷2 ÷2
__________
x = 3
So, the answer is 'B.'
_________________________________________
3.) 4x + 6 - 3x = 12 - 2x - 3x
Again, we combine the like-terms, on both sides of the equal sign:
x + 6 = 12 - 5x
Now, we get both terms with the variable 'x,' to the same side, and, the opposite of subtraction, is addition, so, we're going to add 5x to both sides:
x + 6 = 12 - 5x
+ 5x + 5x
______________
6x + 6 = 12
Now, we subtract 6 from each side, because, the opposite of addition, is subtraction:
6x + 6 = 12
- 6 - 6
_____________
6x = 6
Now, divide by 6, on both sides:
6x = 6
÷ 6 ÷ 6
_____________
x = 1
So, the answer is not 'C.'
_________________________________________
4.) 4x + 6 - 3x = 12x + 2x + 3x
First, we combine the like-terms:
x + 6 = 17x
Next, we get both terms, with the variable, 'x,' to the same side:
x + 6 = 17x
-x -x
_____________
6 = 16x
Now, divide by 16, on both sides:
X = 3/8
So, 'D,' is not the answer.
_______________________
The answer is, 'B.'
I hope this helps!
<span>GH would be the intersection in this case. This is the place where the planes come together. An intersection is where two things come together. This enables an object to create a shape like a box and gives support to the sides that mesh.</span>
Answer: The equation of an ellipse:
(
x
−
h
)
2
a
2
+
(
y
−
k
)
2
b
2
=
1
;
a
>
b
Has vertices at
(
h
±
a
,
k
)
Has foci at
(
h
±
√
a
2
−
b
2
,
k
)
Use the vertices to write 3 equations:
k
=
4
[1]
h
−
a
=
−
6
[2]
h
+
a
=
10
[3]
Use equations [2] and [3] to solve for h and a:
2
h
=
4
h
=
2
a
=
8
Use the focus to write another equation:
8
=
h
+
√
a
2
−
b
2
Substitute values for h and a:
8
=
2
+
√
8
2
−
b
2
6
=
√
64
−
b
2
36
=
64
−
b
2
b
2
=
64
−
36
b
2
=
28
b
=
√
28
Substitute the values into the standard form:
(
x
−
2
)
2
8
2
+
(
y
−
4
)
2
(
√
28
)
2
=
1